2014
DOI: 10.1016/j.marenvres.2013.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Manganese overload affects p38 MAPK phosphorylation and metalloproteinase activity during sea urchin embryonic development

Abstract: a b s t r a c tIn the marine environment, manganese represents a potential emerging contaminant, resulting from an increased production of manganese-containing compounds. In earlier reports we found that the exposure of Paracentrotus lividus sea urchin embryos to manganese produced phenotypes with no skeleton. In addition, manganese interfered with calcium uptake, perturbed extracellular signal-regulated kinase (ERK) signaling, affected the expression of skeletogenic genes, and caused an increase of the hsc70 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
15
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 49 publications
(61 reference statements)
4
15
0
Order By: Relevance
“…Extensive studies using the specific inhibitor SP600125 will help our understanding of a possible link to the JNK signaling pathway. However, phosphorylation of c‐jun is responsive to kinases belonging to different signaling pathways , some of which have already been identified in the sea urchin embryo . In conclusion, the present study demonstrates that the newly identified and characterized Pl ‐jun mRNA is exclusively expressed in a subgroup of skeletogenic cells and, even more excitingly, that the related protein exists in an active form in the nuclei of the same cells.…”
Section: Discussionsupporting
confidence: 66%
“…Extensive studies using the specific inhibitor SP600125 will help our understanding of a possible link to the JNK signaling pathway. However, phosphorylation of c‐jun is responsive to kinases belonging to different signaling pathways , some of which have already been identified in the sea urchin embryo . In conclusion, the present study demonstrates that the newly identified and characterized Pl ‐jun mRNA is exclusively expressed in a subgroup of skeletogenic cells and, even more excitingly, that the related protein exists in an active form in the nuclei of the same cells.…”
Section: Discussionsupporting
confidence: 66%
“…The expression level of p38 MAPK , participating in a signalling cascade in response to different stimuli [33], was affected by heptadienal at the prism and pluteus stages. Very recently, Pinsino et al [44] emphasized the role of p38 MAPK in the regulation of sea urchin embryonic development after exposure to manganese.…”
Section: Discussionmentioning
confidence: 99%
“…65 The p-38 MAPK plays an important role in embryo development (P. lividus) as it is actively involved in the sea urchin embryo protective machinery against different stressors as UVB radiation as well as heavy metals. 55, 85 The 14-3-3 proteins have been shown to play an important role in cellular homeostasis and stress response in sea urchin embryos (P. lividus) and dose-dependently induced by UVB radiations in early and late development. 86 Toxic aldehydes produced by copepods are also able to induced 14-3-3ε gene expression during embryo development.…”
Section: Disposition In Sea Urchin Developing Embryosmentioning
confidence: 99%